PENGARUH PROGRAM PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO PONSEL CELLCOM KALIBOTOBENER PURWOREJO (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
The aim of this research is to determine the effect of promotional programs on consumer purchasing decisions at the Cellcom Kaliboto Bener Purworejo cellphone shop. Data collection and surveys were carried out using questionnaires. Sampling used purposive sampling technique, totaling 32 people. This research uses data analysis methods, simple linear regression, coefficient of determination and t test (partial). Based on the research carried out, the result of the regression equation is Y= 15.889 + 0.768X, which means that if the promotional program variable is equal to zero then the level or magnitude of the variable the purchase decision at Cellcom was 15,889. The contribution of promotional program variables to purchasing decisions is 0.478 or 47.8%, while the remaining 52.2% is influenced by other factors, namely price, product quality, product design, service and others. Partially there is a positive and significant influence between promotional programs on purchasing decisions.